EFFECT OF DIGITAL ELEVATION MODEL MESH SIZE ON GEOMORPHIC INDICES: A CASE STUDY OF THE IVAÍ RIVER WATERSHED - STATE OF PARANÁ, BRAZIL - Santos, Vanessa Cristina Dos; Hage, Mhamad El; Polidori, Laurent; Stevaux, José Cândido (Universidade Federal do Paraná, 2017)
Abstract: Geomorphometry is the science of quantitative description of land surface morphology by the mean of geomorphic indices extracted from Digital Elevation Models (DEMs). The analysis of these indices is the first and most common procedure performed in several geoscience-related subjects. This study aims to assess the impact of mesh size degradation on different local and regional geomorphic indices extracted for GDEM and TOPODATA DEMs. Thus, these DEMs, having a mesh size of 30 m, were subsampled to 60, 120 and 240 m and then geomorphic indices were calculated using the full resolution DEM and the subsampled ones. Depending on their behavior, these indices are then classified into stable and unstable. The results show that the most affected indices are slope and hydrographic indices such as Strahler order, stream sinuosity and fractal dimension and watershed perimeter, whereas elevation remains stable. It also shows that the effect depends on the presence of the canopy and geological structures in the studied area.

Resumo: A geomorfometria é a ciência da descrição quantitativa da morfologia da superfície terrestre por meio de índices geomórficos extraídos de Modelos Digitais de Elevação (MDEs). A análise destes índices é um dos primeiros e mais comuns procedimentos executados em estudos relacionados a geociência. Este estudo tem como objetivo avaliar o impacto da degradação da dimensão da malha (mesh size) sobre diferentes índices geomórficos locais e regionais extraídos dos MDEs GDEM e TOPODATA. Estes MDEs, ambos com dimensão original da malha de 30 m, foram reamostrados para 60, 120 e 240 m, sendo em seguida calculados os índices geomórficos, tanto para a dimensão original quanto para as reamostras. Dependendo do seu comportamento, estes índices foram classificados em estáveis e instáveis. Os resultados mostram que os índices mais afetados são a declividade e os índices hidrográficos como a ordem de Strahler, a sinuosidade, a dimensão fractal e o perímetro da bacia, enquanto que a elevação permanece estável. Os resultados também mostram que os efeitos dependem da presença do dossel florestal e das estruturas geológicas na área estudada.
O efeito da dimensão da malha de Modelos Digitais de Elevação sobre os índices geomórficos: O estudo de caso da bacia hidrográfica do rio Ivaí - Estado do Paraná, Brasil
Keywords: Geomorphic indices; Digital Elevation Model; Mesh Size; Scale; Índices geomórficos; Modelo Digital de Elevação; dimensão da malha, escala